Study of Characteristic Strength of Concrete by Partial Replacement of Cement with Ceramic Waste Powder A Review - Harikrishana Chaudhary; Mr. Rahul Kumar Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2025)
In the construction industry, ceramic wall tiles are utilised as building materials. Due to this manufacturing variation, the temperature in the kiln fluctuates from 200°C to 1200°C, and the material possesses pozzolanic reactivity. During various manufacturing processes, 5–10% of the production in the ceramics industry is lost. The waste from the ceramic factory was dumped nearby, resulting in environmental pollution that harmed the nearby fields and residences. Therefore, incorporating ceramic waste powder in concrete would help save energy and safeguard the environment in a variety of ways. This research is based on secondary as well as primary data. This investigation highlighted the nature of concrete strength variation with increasing ceramic waste. The maximum strength gain occurs when 30% of cement is replaced by ceramic waste.